Passivity based analysis and design of urban drainage control systems (2023)
This paper proposes a passivity based approach for the design of control schemes for urban drainage systems (UDSs). First, we demonstrate equilibrium-independent passivity (EIP) of replicator dynamics (RD). Then, we analyze two types of UDS subsystems and use passivity arguments to conclude stability of a closed loop model with RD. Lastly, we propose a distributed consensus assisted algorithm for a network of subsystems and provide simulations showing advantages in its performance.